Theory of electronic properties of amorphous silicon-carbon alloys: effects of short-range disorder - Denteneer, P. J H; Kelires, Pantelis C. (My University, 1993)
Homopolar (like-atom) bonding and thresfold carbon coordination are found to drastically affect the electronic properties of amorphous silicon-carbon alloys. First-principles pseudopotential calculations based on amorphous geometries obtained from Monte Carlo empirical simulations show that incorporating C in Si-rich samples, in tetrahedral arrangements with heteropolar bonds only, increases the energy gap. This tendency is drastically reversed in C-rich samples because of graphitelike geometries. Like-atom bonds, in samples of all compositions, reduce the gap as well. The maximum gap is reached in samples of near-stoichiometric composition.
Keywords: Carbon; Geometry; Monte Carlo method; Mathematical models; Silicon alloys; Molecular dynamics